A microspectroscopic insight into the resistivity switching of individual Ag-TCNQ nanocrystals - Rösner, Benedikt; Ran, Ke; Butz, Benjamin; Schmidt, Ute; Spiecker, Erdmann; Fink, Rainer (Physical Chemistry Chemical Physics, 2015)
We investigate the resistivity switching in individual Ag-TCNQ wires with on/off-ratios of up to 103. Raman and soft X-ray absorption microspectroscopy studies disclose reverse charge transfer. Quantifying of the fraction of neutral TCNQ within the switched material yields values up to 22.3%. These findings expedite the understanding of the switching process in Ag-TCNQ nanowires.

Butterfly gyroid nanostructures as a time-frozen glimpse of intracellular membrane development. - Wilts, Bodo D.; Apeleo Zubiri, Benjamin; Klatt, Michael A.; Butz, Benjamin; Fischer, Michael G.; Kelly, Stephen T.; Spiecker, Erdmann; Steiner, Ullrich; Schroeder-Turk, Gerd E. (Science Advances, 2017)
The formation of the biophotonic gyroid material in butterfly wing scales is an exceptional feat of evolutionary engineering of functional nanostructures. It is hypothesized that this nanostructure forms by chitin polymerization inside a convoluted membrane of corresponding shape in the endoplasmic reticulum. However, this dynamic formation process, including whether membrane folding and chitin expression are simultaneous or sequential processes, cannot yet be elucidated by in vivo imaging. We report an unusual hierarchical ultrastructure in the butterfly Thecla opisena that, as a solid material, allows high-resolution three-dimensional microscopy. Rather than the conventional polycrystalline space-filling arrangement, a gyroid occurs in isolated facetted crystallites with a pronounced size gradient. When interpreted as a sequence of time-frozen snapshots of the morphogenesis, this arrangement provides insight into the formation mechanisms of the nanoporous gyroid material as well as of the intracellular organelle membrane that acts as the templat

Carbon Nanodots: Toward a Comprehensive Understanding of Their Photoluminescence - Strauß, Volker; Margraf, Johannes; Dolle, Christian; Butz, Benjamin; Nacken, Thomas; Walter, Johannes; Bauer, Walter; Peukert, Wolfgang; Spiecker, Erdmann; Clark, Timothy; Guldi, Dirk Michael (Journal of the American Chemical Society, 2014)
We report the characterization of carbon nanodots (CNDs) synthesized under mild and controlled conditions, that is, in a microwave reactor. The CNDs thus synthesized exhibit homogeneous and narrowly dispersed optical properties. They are thus well suited as a testbed for studies of the photophysics of carbon-based nanoscopic emitters. In addition to steady-state investigations, time-correlated single-photon counting, fluorescence up-conversion, and transient pump probe absorption spectroscopy were used to elucidate the excited-state dynamics. Moreover, quenching the CND-based emission with electron donors or acceptors helped shed light on the nature of individual states. Density functional theory and semiempirical configuration-interaction calculations on model systems helped understand the fundamental structure-property relationships for this novel type of material.

Coexistence of both gyroid chiralities in individual butterfly wing scales of Callophrys rubi - Winter, Benjamin; Butz, Benjamin; Dieker, Christel; Schroeder-Turk, Gerd E.; Mecke, Klaus; Spiecker, Erdmann (Proceedings of the National Academy of Sciences of the United States of America, 2015)
The wing scales of the Green Hairstreak butterfly Callophrys rubi consist of crystalline domains with sizes of a few micrometers, which exhibit a congenitally handed porous chitin microstructure identified as the chiral triply periodic single-gyroid structure. Here, the chirality and crystallographic texture of these domains are investigated by means of electron tomography. The tomograms unambiguously reveal the coexistence of the two enantiomeric forms of opposite handedness: the left- and right-handed gyroids. These two enantiomers appear with nonequal probabilities, implying that molecularly chiral constituents of the biological formation process presumably invoke a chiral symmetry break, resulting in a preferred enantiomeric form of the gyroid structure. Assuming validity of the formation model proposed by Ghiradella H (1989) J Morphol 202(1): 69-88 and Saranathan V, et al. (2010) Proc Natl Acad Sci USA 107(26): 11676-11681, where the two enantiomeric labyrinthine domains of the gyroid are connected to the extracellular and intra-SER spaces, our findings imply that the structural chirality of the single gyroid is, however, not caused by the molecular chirality of chitin. Furthermore, the wing scales are found to be highly textured, with a substantial fraction of domains exhibiting the < 001 > directions of the gyroid crystal aligned parallel to the scale surface normal. Both findings are needed to completely understand the photonic purpose of the single gyroid in gyroid-forming butterflies. More importantly, they show the level of control that morphogenesis exerts over secondary features of biological nanostructures, such as chirality or crystallographic texture, providing inspiration for biomimetic replication strategies for synthetic self-assembly mechanisms.
Keywords: electron tomography; chirality; crystallographic texture; photonic crystal; butterfly wing scales

Controlled In Situ PbSe Quantum Dot Growth around Single-Walled Carbon Nanotubes: A Noncovalent PbSe-SWNT Hybrid Structure - Schornbaum, Julia; Winter, Benjamin; Schießl, Stefan; Butz, Benjamin; Spiecker, Erdmann; Zaumseil, Jana (Chemistry of Materials, 2013)
We developed a simple method of synthesizing noncovalently linked hybrids of PbSe quantum dots (QDs) and single-walled carbon nanotubes (SWNTs). The PbSe QDs grow around the SWNTs without any linker molecule or chemical modification of the SWNTs. We are able to control the size and shape of the QDs attached to the SWNTs by varying the synthesis conditions and elucidate the three-dimensional (3D) morphology and atomic structure of the half-ring-shaped PbSe QDs bonded to the SWNTs using scanning transmission electron microscopy (STEM) tomography and high-resolution transmission electron microscopy (HRTEM). The PbSe QDs not only assemble on the SWNT bundles, but they actually grow around them. The growth of the PbSe QDs around SWNT sidewalls is favored over the growth of spherical particles in solution, probably due to dipole stabilization by the large pi-electron system of the SWNTs.
Keywords: hybrid material; PbSe quantum dots; single-walled carbon nanotubes; electron tomography

Crystal Shape Engineering of Silicon Nanoparticles in a Thermal Aerosol Reactor - Koermer, Richard; Butz, Benjamin; Spiecker, Erdmann; Peukert, Wolfgang (Crystal Growth & Design, 2012)
In this work, the capability of gas phase synthesis for crystal shape engineering of silicon nanoparticles (SiNP) in a hot wall reactor is demonstrated. Therefore, the necessary boundary conditions for the formation of monodisperse spherical SiNP as well as octahedral shaped particles from silane pyrolysis are systematically deduced. The different shapes of the SiNP are ascribed to different growth regimes (reaction limitation, diffusion limitation) depending on the global process parameters. Single crystalline, defect-free, spherical particles with a mean diameter of 30 nm (geometric standard deviation below 1.1) and octahedra with a mean edge length of about 100 nm could be obtained solely by process parameter adjustment. Particle size and shape as well as crystallinity were characterized by scanning electron microscopy and X-ray diffraction. The inner structure and faceting of the particles was analyzed in detail by high resolution transmission electron microscopy. A model which elucidates the orientation relation between inner silicon structure and the particle shape is derived for the octahedra.

Direct in situ transmission electron microscopy observation of Al push up during early stages of the Al-induced layer exchange - Birajdar, Balaji; Antesberger, T.; Butz, Benjamin; Stutzmann, Martin; Spiecker, Erdmann (Scripta Materialia, 2012)
The mechanism of Al transport during Al-induced layer exchange and crystallization of amorphous Si (a-Si) has been investigated by in situ and analytical transmission electron microscopy. Significant grain boundary realignment and coarsening of Al grains close to the Si crystallization growth front as well as push up of excess Al into the a-Si layer at distances even a few micrometers away from the crystallization front were observed. Stress-mediated diffusion of Al is postulated to explain the experimental observations. (C) 2012 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Thin films; Solar cells; Crystallization; Analytical electron microscopy; Diffusion

Dislocations in bilayer graphene - Butz, Benjamin; Dolle, Christian; Niekiel, Florian; Weber, Konstantin; Waldmann, Daniel; Weber, Heiko B.; Meyer, Bernd; Spiecker, Erdmann; Spiecker, Erdmann (Nature, 2014)
Dislocations represent one of the most fascinating and fundamental concepts in materials science. Most importantly, dislocations are the main carriers of plastic deformation in crystalline materials. Furthermore, they can strongly affect the local electronic and optical properties of semiconductors and ionic crystals. In materials with small dimensions, they experience extensive image forces, which attract them to the surface to release strain energy. However, in layered crystals such as graphite, dislocation movement is mainly restricted to the basal plane. Thus, the dislocations cannot escape, enabling their confinement in crystals as thin as only two monolayers. To explore the nature of dislocations under such extreme boundary conditions, the material of choice is bilayer graphene, the thinnest possible quasi-two-dimensional crystal in which such linear defects can be confined. Homogeneous and robust graphene membranes derived from high-quality epitaxial graphene on silicon carbide provide an ideal platform for their investigation. Here we report the direct observation of basal-plane dislocations in freestanding bilayer graphene using transmission electron microscopy and their detailed investigation by diffraction contrast analysis and atomistic simulations. Our investigation reveals two striking size effects. First, the absence of stacking-fault energy, a unique property of bilayer graphene, leads to a characteristic dislocation pattern that corresponds to an alternating ABAC change of the stacking order. Second, our experiments in combination with atomistic simulations reveal a pronounced buckling of the bilayer graphene membrane that results directly from accommodation of strain. In fact, the buckling changes the strain state of the bilayer graphene and is of key importance for its electronic properties. Our findings will contribute to the understanding of dislocations and of their role in the structural, mechanical and electronic properties of bilayer and few-layer graphene. © 2014 Macmillan Publishers Limited. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2014.nat.dphy.IAP.LAP.disloc

Formation of a protective layer during IEC(b) test of epoxy resin loaded with silica nanoparticles - Meichsner, Christian; Clark, Timothy; Groeppel, Peter; Winter, Benjamin; Butz, Benjamin; Spiecker, Erdmann (IEEE Transactions on Dielectrics and Electrical Insulation, 2012)
The erosion resistance of materials against partial discharges (PD) is a useful first indicator of their suitability for use as high voltage insulators. Epoxy resin-based composites loaded with different concentrations of silica nanoparticles were exposed to high voltage stress via an IEC(b) electrode. Laser scanning analysis was used to investigate the eroded volume and the erosion depth. The aged samples were investigated by transmission electron microscopy (TEM) analysis and scanning transmission electron microscopy (STEM), which show the formation of a protective layer of partially fused nanoparticles. The results suggest that improved erosion resistance against PD using the IEC(b) electrode is caused by the in situ formation of a protective layer consisting of sintered nanoparticles.

Formation of CdS in Supramolecular Dendrimer-Dye Assemblies: Electrostatic and Electrostatic-Coordination Templating - Düring, Jasmin; Butz, Benjamin; Spiecker, Erdmann; Gröhn, Franziska (Macromolecules, 2015)
A novel concept for the formation of organic inorganic hybrid nanostructures based on a tunable supra-molecular templating mechanism involving several types of noncovalent interactions is presented. Different organic inorganic hybrid structures with narrow size distributions composed of a cationic dendrimer, an oppositely charged divalent diazo dye, and CdS can be created: First, larger supramolecular structures consisting of several 100 to 1000 dendrimers is built based on ionic and pi-pi interaction. Second, with this self-assembled template, the hybrid nanostructure forms based on electrostatics and coordination interaction. The influence on shape and internal structure of the supramolecular hybrid architectures was investigated. A size control of the assemblies is possible in a range of 60-420 nm. The prospect to direct self-assembly and templating through the controlled combination of different noncovalent interactions potentially allows to create tailor-made systems for various applications.

Fully Patterned Low-Voltage Transparent Metal Oxide Transistors Deposited Solely by Chemical Spray Pyrolysis - Faber, Hendrik; Butz, Benjamin; Dieker, Christel; Spiecker, Erdmann; Halik, Marcus (Advanced Functional Materials, 2013)
All-inorganic transparent thin-film transistors deposited solely by the solution processing method of spray pyrolysis are reported. Different precursor materials are employed to create conducting and semiconducting species of ZnO acting as electrodes and active channel material, respectively, as well as zirconium oxide as gate dielectric layer. Additionally, a simple stencil mask system provides sufficient resolution to realize the necessary geometric patterns. As a result, fully functional low-voltage n-type transistors with a mobility of 0.18 cm2 V−1 s−1 can be demonstrated via a technique that bears the potential for upscaling. A detailed microscopic evaluation of the channel region by electron diffraction, high-resolution and analytical TEM confirms the layer stacking and provides detailed information on the chemical composition and nanocrystalline nature of the individual layers.

Functionalization of graphene by electrophilic alkylation of reduced graphite - Englert, Jan; Knirsch, Kathrin; Dotzer, Christoph; Butz, Benjamin; Hauke, Frank; Hirsch, Andreas; Spiecker, Erdmann (Chemical Communications, 2012)
The reaction of Na/K-reduced graphite with hexyliodide represents a new, versatile and mild approach to synthesize alkylated graphene derivatives, which were characterized by a combination of Raman spectroscopy, TEM and TGA/MS analysis. © The Royal Society of Chemistry 2012.

Gas phase synthesis of anisotropic silicon germanium hybrid nanoparticles - Mehringer, Christian; Wagner, Richard; Jakuttis, Thomas; Butz, Benjamin; Spiecker, Erdmann; Peukert, Wolfgang (Journal of Aerosol Science, 2014)
We demonstrate the capability of hot wall reactor gas phase synthesis to produce germanium (Ge) on silicon (Si) anisotropic particles. A two stage reactor setup is used to produce silicon nanoparticles (SiNPs) of 29.6 nm in diameter with a very narrow size distribution and to deposit Ge on them. The gaseous precursors are monosilane (SiH4) and monogermane (GeH4). In a SEM study Ge patch formation on the SiNPs due to Stranski–Krastanov growth is observed. The patch size as well as the number of patches per SiNP is dependent on the process temperature and the GeH4 partial pressure. By varying these parameters it is possible to synthesize Janus-like particles with only one e.g. facetted Ge patch per SiNP, as well as patchy particles carrying an average of four to eight patches. HRTEM analysis shows, that the Ge grows epitaxial and crystalline on the surface of the SiNPs. From geometric phase analysis (GPA) the termination of inserted (220) half planes corresponding to misfit dislocations can be deduced, indicating a largely relaxed lattice in the Ge patches. A continuous tilt of the (111) lattice planes in the Si core below a Ge patch indicates that elastic deformation also contributes to the strain relaxation.

Germanium-silicon alloy and core-shell nanocrystals by gas phase synthesis - Mehringer, Christian; Kloner, Christian; Butz, Benjamin; Winter, Benjamin; Spiecker, Erdmann; Peukert, Wolfgang (Nanoscale, 2015)
In this work we present a novel route to synthesize well defined germanium-silicon alloy (GexSi1-x) and core-shell nanocrystals (NCs) employing monosilane (SiH4) and monogermane (GeH4) as precursors in a continuously operated two-stage hot-wall aerosol reactor setup. The first hot-wall reactor stage (HWR I) is used to produce silicon (Si) seed particles from SiH4 pyrolysis in Argon (Ar). The resulting seeding aerosol is fed into the second reactor stage (HWR II) and a mixture of SiH4 and GeH4 is added. The ratio of the precursors in the feed, their partial pressures, the synthesis temperature in HWR II and the overall pressure are varied depending on the desired morphology and composition. Alloy particle production is achieved in the heterogeneous surface reaction regime, meaning that germanium (Ge) and Si are deposited on the seed surface simultaneously. The NCs can be synthesized with any desired composition, whilst maintaining a mean diameter around 30 nm with a geometric standard deviation (GSD) around 1.25. The absorption behavior and the related fundamental optical band gap energy in dependence on the alloy composition are exemplarily presented. They prove the possibility to tailor NC properties for electronical and opto-electronical applications. In the homogeneous gas phase reaction regime facetted Ge-Si core-shell structures are accessible. The Ge deposition on the seeds precedes the Si deposition due to different gas phase reaction kinetics of the precursors. The Si layer grows epitaxially on the Ge core and is around 5 nm thick.

Highly Intact and Pure Oxo-Functionalized Graphene:Synthesis and Electron-Beam-Induced Reduction - Butz, Benjamin; Dolle, Christian; Halbig, Christian Eberhard; Spiecker, Erdmann; Eigler, Siegfried (Angewandte Chemie International Edition, 2016)
Controlling the chemistry of graphene is necessary to enable applications in materials and life sciences. Research beyond graphene oxide is targeted to avoid the highly defective character of the carbon framework. Herein, we show how to optimize the synthesis of oxo-functionalized graphene (oxo-G) to prepare high-quality monolayer flakes that even allow for direct transmission electron microscopy investigation at atomic resolution (HRTEM). The role of undesired residuals is addressed and sources are eliminated. HRTEM provides clear evidence for the exceptional integrity of the carbon framework of such oxo-G sheets.The patchy distribution of oxo-functionality on the nm-scale,observed on our highly clean oxo-G sheets,corroborates theoretical predictions. Moreover, defined electron-beam irradiation facilitates gentle defunctionalization of oxo-G sheets, a new route towards clean graphene, which is a breakthrough for localized graphene chemistry.

Highly Integrated Organic–Inorganic Hybrid Architectures by Noncovalent Exfoliation of Graphite and Assembly with Zinc Oxide Nanoparticles - Marcia, Mario; Vinh, Chau; Dolle, Christian; Abellan Saez, Gonzalo; Schönamsgruber, Jörg; Schunk, Torsten; Butz, Benjamin; Spiecker, Erdmann; Hauke, Frank; Hirsch, Andreas (Advanced Materials Interfaces, 2016)
Liquid-phase exfoliated few-layer graphene flakes are noncovalently functionalized with tailor-made cationic water-soluble perylene diimides. By using a straightforward dip-coating approach, homogeneous ultrathin films consisting of interpenetrated nanoarchitectures can be achieved by incorporation of anionic ZnO nanoparticles. These 0D/2D assemblies pave the way for the development of novel graphene-based composite materials.
Keywords: graphene; hybrid materials; layer-by-layer assembly; nanoparticles; supramolecular chemistry

Highly resolved analysis of the chemistry and mechanical properties of an a-C:H coating system by nanoindentation and auger electron spectroscopy - Schmid, Christoph; Maier, Verena; Schaufler, Jens; Butz, Benjamin; Spiecker, Erdmann; Meier, S.; Göken, Mathias; Durst, Karsten (Thin Solid Films, 2013)
The small-angle cross-section method was applied to a multi-layered hydrogenated amorphous carbon coating (a-C:H) system deposited by plasma enhanced chemical vapour deposition. The investigated system consists of a silicon rich adhesion layer and an adjacent ramp layer with a graded chemical composition to the a-C:H coating. The mechanical properties and the corresponding chemical gradients of the coating system were analysed by a combination of the small-angle cross-section method together with auger electron spectroscopy and nanoindentation. Furthermore, energy filtered transmission electron microscopy on a thin lamella was used to check the reliability of the auger electron spectroscopy results. It was found that local gradients in the chemical composition within the coating relate well to gradients observed in the local mechanical properties. The used combination of the different methods enables to resolve the correlation between the microstructure, chemical composition and mechanical properties of thin film systems with high spatial resolution. (c) 2012 Elsevier B.V. All rights reserve
Keywords: a-C:H; Nanoindentation; Small-angle cross-section; Focused ion beam; Adhesion layer; Chemical composition; DLC

ITO-Free and Fully Solution-Processed Semitransparent Organic Solar Cells with High Fill Factors - Guo, Fei; Zhu, Xiangdong; Forberich, Karen; Krantz, Johannes; Stubhan, Tobias; Salinas Batallas, Michael; Halik, Marcus; Spallek, Stefanie; Butz, Benjamin; Spiecker, Erdmann; Ameri, Tayebeh; Li, Ning; et al. (Advanced Energy Materials, 2013)
Organic photovoltaic (OPV) solar cells that can be simply processed from solution are in the focus of the academic and industrial community because of their enormous potential to reduce cost. One big challenge in developing a fully solution-processed OPV technology is the design of a well-performing electrode system, allowing the replacement of ITO. Several solution-processed electrode systems were already discussed, but none of them could match the performance of ITO. Here, we report efficient ITO-free and fully solution-processed semitransparent inverted organic solar cells based on silver nanowire (AgNW) electrodes. To demonstrate the potential of these AgNW electrodes, they were employed as both the bottom and top electrodes. Record devices achieved fill factors as high as 63.0%, which is comparable to ITO based reference devices. These results provide important progress for fully printed organic solar cells and indicate that ITO-free, transparent as well as non-transparent organic solar cells can indeed be fully solution-processed without losses. Indium tin oxide (ITO)-free and fully solution-processed organic solar cells are demonstrated by employing AgNW as both the bottom and top electrodes, in conjunction with Al-ZnO and poly(3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS) as charge extraction layers. Devices with electrical fill factor (FF) up to 63.0% and fully retained open circuit voltage (V) are achieved, indicating that superior optoelectronic and film quality properties of the two interlayers are perfectly compatible to AgNW electrodes. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Linear magnetoresistance in mosaic-like bilayer graphene - Kißlinger, Ferdinand; Ott, Christian; Heide, Christian; Kampert, Erik; Butz, Benjamin; Spiecker, Erdmann; Shallcross, Sam; Weber, Heiko B. (Nature Physics, 2015)
The magnetoresistance of conductors usually has a quadratic dependence on magnetic field(1), however, examples exist of non-saturating linear behaviour in diverse materials(2-6). Assigning a specific microscopic mechanism to this unusual phenomenon is obscured by the co-occurrence and interplay of doping, mobility fluctuations and a polycrystalline structure(7,8). Bilayer graphene has virtually no doping fluctuations, yet provides a built-in mosaic tiling due to the dense network of partial dislocations(9,10). We present magnetotransport measurements of epitaxial bilayer graphene that exhibits a strong and reproducible linear magnetoresistance that persists to B = 62 T at and above room temperature, decorated by quantum interference effects at low temperatures. Partial dislocations thus have a profound impact on the transport properties in bilayer graphene, a system that is frequently assumed to be dislocation-free. It further provides a clear and tractable model system for studying the unusual properties of mosaic conductors.

Linking photo- and redoxactive phthalocyanines covalently to graphene - Ragoussi, Maria-Eleni; Malig, Jenny; Katsukis, Georgios; Butz, Benjamin; Spiecker, Erdmann; De La Torre, Gema; Torres, Tomas; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2012)
"Green" graphene: For the first time, the covalent attachment of a light-harvesting and electron-donating phthalocyanine to the basal plane of few-layer graphene is reported (see picture). Physicochemical characterizations reveal an ultrafast charge separation from the photoexcited phthalocyanine to few-layer graphene followed by a slower charge recombination. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Local temperature measurement in TEM by parallel beam electron diffraction - Niekiel, Florian; Kraschewski, Simon; Müller, Julian; Butz, Benjamin; Spiecker, Erdmann (Ultramicroscopy, 2017)
With the recent advances in instrumentation pushing the limits of in situ transmission electron microscopy, the question of local sample temperature comes into focus again. In this work the applicability of parallel beam electron diffraction to locally measure and monitor the sample temperature in TEM is assessed, with applications for in situ heating experiments in mind. With Au nanoparticles applied to the sample surface, temperature is measured in the range from RT to 890°C by evaluating the change in scattering angle upon thermal expansion. Repeated measurements at constant temperature reveal a statistical precision of the method as good as 2.8K. The applicability to locally measure the temperature is demonstrated mapping the temperature gradient across a heating chip. Owing to instantaneous response of thermal expansion to temperature changes, the method is well suited for monitoring even quick temperature changes, as demonstrated by quenching experiments. In order to enable extensive in situ studies, an evaluation method capable of processing large datasets with high precision is developed. Beam parallelity is identified as crucial experimental prerequisite and a routine is established, optimizing the microscope alignment in terms of beam parallelity. Apart from establishing a procedure for local temperature measurement, the present work demonstrates the unique capabilities of MEMS-based in situ heating equipment.
Keywords: Beam parallelity; In situ microscopy; Metallic nanoparticles; Microscope alignment; Temperature measurement; Transmission electron microscopy

Microstructure of veneered zirconia after surface treatments: A TEM study - Grigore, Alexandra; Spallek, Stefanie; Petschelt, Anselm; Butz, Benjamin; Spiecker, Erdmann; Lohbauer, Ulrich (Dental Materials, 2013)
Signcance. Regardless of the treatment protocol and produced roughness, the veneering ceramic perfectly sealed the zirconia surface. XRD showed an increased amount of monoclinic phase on the surface treated zirconia. However after thermal treatment, the monoclinic phase was re-transformed into the tetragonal polymorph. TEM/SAED analysis has found indication for a greater extend of the monoclinic transformation into the bulk zirconia compared to the treatment related defective zone depth. (C) 2013 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Y-TZP; X-ray diffraction; Martensitic transformation; Sandblasting; Bur drilling; Annealing

Protective Layer of Al2O3 Nanocomposites and Surface Composition after Electrical Stress - Meichsner, Christian; Clark, Timothy; Groeppel, Peter; Winter, Benjamin; Butz, Benjamin; Spiecker, Erdmann (IEEE Transactions on Dielectrics and Electrical Insulation, 2015)
The performance of nanocomposites for improved resistance to electrical discharges has resulted in increased interest in nano-loaded thermosetting resins. First assessments of the performance of new systems can be obtained by a plate-electrode construction according to IEC(b). Epoxy resins loaded with different amounts of spherical alumina particles were tested following this procedure and parameters such as erosion depth and standardized volume analyzed. Transmission electron microscopy (TEM) and a three-dimensional (3D) reconstruction using electron tomography were used to determine the particle size distribution. TEM analysis after preparation of the eroded samples indicates the advantages and disadvantages of using alumina nanoparticles to improve the erosion resistance and showed a novel effect of the surface-grafted polysiloxanes. A comparison with conventional nano-silica-loaded resins reveals that the lower sintering tendency of Al2O3 is important.
Keywords: Alumina; epoxy resin; erosion resistance; nanoparticles; transmission electron microscopy; electron tomography

Prototyping of catalyst pore-systems by a combined synthetic, analytical and computational approach: Application to mesoporous TiO2 - Novak, Vladimir; Ortel, Erik; Winter, Benjamin; Butz, Benjamin; Paul, Benjamin; Koci, Petr; Marek, Milos; Spiecker, Erdmann; Kraehnert, Ralph (Chemical Engineering Journal, 2014)
We propose a strategy that enables virtual prototyping and computational optimization of the pore system of a solid catalyst. The method combines template-assisted synthesis of porous metal oxides with tunable pore-space morphology, 3D imaging of the catalysts nanostructure by the state-of-the-art electron tomography in HAADF STEM mode, and multi-scale mathematical modeling that provides computational evaluation of the pore size distribution, effective diffusivity and tortuosity in the reconstructed system as well as macroscopic performance of the catalytic layer in terms of reactant conversion. This general approach is demonstrated on mesoporous TiO2 layers. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: Catalyst; Nanocasting; Synthesis; Electron tomography; Multi-scale mathematical modeling; Diffusion

Quantitative evaluation of size selective precipitation of Mn-doped ZnS quantum dots by size distributions calculated from UV/Vis absorbance spectra - Segets, Doris; Komada, So; Butz, Benjamin; Spiecker, Erdmann; Mori, Yasushige; Peukert, Wolfgang (Journal of Nanoparticle Research, 2013)
We demonstrate the quantitative evaluation of the sharp classification of manganese-doped zinc sulfide (ZnS:Mn) quantum dots by size selective precipitation. The particles were characterized by the direct conversion of absorbance spectra to particle size distributions (PSDs) and high-resolution transmission electron micrographs (HRTEM). Gradual addition of a poor solvent (2-propanol) to the aqueous colloid led to the flocculation of larger particles. Though the starting suspension after synthesis had an already narrow PSD between 1.5 and 3.2 nm, different particle size fractions were subsequently isolated by the careful adjustment of the good solvent/poor solvent ratio. Moreover, due to the fact that for the analysis of the classification results the size distributions were available, an in-depth understanding of the quality of the distinct classification steps could be achieved. From the PSDs of the feed, as well as the coarse and the fine fractions with their corresponding yields determined after each classification step, an optimum after the first addition of poor solvent was identified with a maximal separation sharpness κ as high as 0.75. Only by the quantitative evaluation of classification results leading to an in-depth understanding of the relevant driving forces, a future transfer of this lab scale post-processing to larger quantities will be possible.

Robust graphene membranes in a silicon carbide frame - Waldmann, Daniel; Butz, Benjamin; Bauer, Sebastian; Englert, Jan; Jobst, Johannes; Ullmann, Konrad; Fromm, Felix; Ammon, Maximilian Michael; Enzelberger-Heim, Michael; Hirsch, Andreas; Maier, Sabine; Schmuki, Patrik; et al. (ACS nano, 2013)
We present a fabrication process for freely suspended membranes consisting of bi- and trilayer graphene grown on silicon carbide. The procedure, involving photoelectrochemical etching, enables the simultaneous fabrication of hundreds of arbitrarily shaped membranes with an area up to 500 μm(2) and a yield of around 90%. Micro-Raman and atomic force microscopy measurements confirm that the graphene layer withstands the electrochemical etching and show that the membranes are virtually unstrained. The process delivers membranes with a cleanliness suited for high-resolution transmission electron microscopy (HRTEM) at atomic scale. The membrane, and its frame, is very robust with respect to thermal cycling above 1000 °C as well as harsh acidic or alkaline treatment.

Silver-assisted colloidal synthesis of gold patchy particles with tunable patchiness - Bao, Huixin; Butz, Benjamin; Zhou, Zhou; Spiecker, Erdmann; Hartmann, Martin; Klupp Taylor, Robin (Langmuir, 2012)
Patchy particles possessing heterogeneous surface composition show great promise as self-organizing building blocks for new classes of hierarchical functional structures. A major hurdle is the scalable synthesis of stable patches on nanosized core particles with arbitrarily defined patch number and coverage. So far, few methods have been reported which could be expected to meet these challenges. Recently we described the heterogeneous nucleation and growth of silver patches on silica nanospheres via a template free colloidal route. The patches produced, although tunable in size and number and showing interesting plasmon resonant properties, were rather unstable and degraded rapidly during attempts to process them further. In the present work, therefore, we set out to explore if related approaches can be employed to produce patchy particles involving gold, which is known to be more stable. The differences between typical patch precursors Ag+ and [AuClx (OH)4-x]- and their respective interactions with amorphous silica make this a significant challenge. We show that preformed small silver patches in addition to the presence of a reducing agent are necessary for the formation of gold patches conformal to the silica nanosphere surface. Systematic study of the process parameters and their influence on the patchiness as well as in-depth analytical TEM investigation of the patch composition reveal that patches spread over the silica surface via a cycle of galvanic dissolution and redeposition of silver. The resulting gold patchy particles remain stable during subsequent storage or washing and display tunable plasmon resonances within the visible and near-IR spectrum.
EAM Import::2019-03-13

Silver-Assisted Colloidal Synthesis of Stable, Plasmon Resonant Gold Patches on Silica Nanospheres - Bao, Huixin; Butz, Benjamin; Zhou, Zhou; Spiecker, Erdmann; Hartmann, Martin; Klupp Taylor, Robin (Langmuir, 2012)
Patchy particles possessing heterogeneous surface composition show great promise as self-organizing building blocks for new classes of hierarchical functional structures. A major hurdle is the scalable synthesis of stable patches on nanosized core particles with arbitrarily defined patch number and coverage. So far, few methods have been reported which could be expected to meet these challenges. Recently, we described the heterogeneous nucleation and growth of silver patches on silica nanospheres via a template free colloidal route. The patches produced, although tunable in size and number and showing interesting plasmon resonant properties, were rather unstable and degraded rapidly during attempts to process them further. In the present work, therefore, we set out to explore if related approaches can be employed to produce patchy particles involving gold, which is known to be more stable. The differences between typical patch precursors Ag+ and [AuClx(OH)(4-x)](-) and their respective interactions with amorphous silica make this a significant challenge. We show that preformed small silver patches in addition to the presence of a reducing agent are necessary for the formation of gold patches conformal to the silica nanosphere surface. Systematic study of the process parameters and their influence on the patchy particle morphology as well as in-depth analytical transmission electron microscopy investigation of the patch composition reveal that patches spread over the silica surface via a cycle of galvanic dissolution and redeposition of silver. The resulting gold patchy particles remain stable during subsequent storage or washing and display tunable plasmon resonances within the visible and near-IR spectrum.
Keywords: colloid; plasmon; resonant; nanospheres; silica; self; organizing; heterogeneous; nucleation

Solution-Processed Parallel Tandem Polymer Solar Cells Using Silver Nanowires as Intermediate Electrode - Guo, Fei; Kubis, Peter; Li, Ning; Przybilla, Thomas; Matt, Gebhard; Stubhan, Tobias; Ameri, Tayebeh; Butz, Benjamin; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (Acs Nano, 2014)
Tandem architecture is the most relevant concept to overcome the efficiency limit of single-junction photovoltaic solar cells. Series-connected tandem polymer solar cells (PSCs) have advanced rapidly during the past decade. In contrast, the development of parallel-connected tandem cells is lagging far behind due to the big challenge in establishing an efficient interlayer with high transparency and high in-plane conductivity. Here, we report all-solution fabrication of parallel tandem PSCs using silver nanowires as intermediate charge collecting electrode. Through a rational interface design, a robust interlayer is established, enabling the efficient extraction and transport of electrons from subcells. The resulting parallel tandem cells exhibit high fill factors of similar to 60% and enhanced current densities which are identical to the sum of the current densities of the subcells. These results suggest that solution-processed parallel tandem configuration provides an alternative avenue toward high performance photovoltaic devices.
Keywords: parallel-tandem; polymer solar cells; solution-processed; silver nanowires

Switching behaviour of individual Ag-TCNQ nanowires: an in situ transmission electron microscopy study - Ran, Ke; Rösner, Benedikt; Butz, Benjamin; Fink, Rainer; Spiecker, Erdmann (Nanotechnology, 2016)
The organic semiconductor silver-tetracyanoquinodimethane (Ag-TCNQ) exhibits electrical switching and memory characteristics. Employing a scanning tunnelling microscopy setup inside a transmission electron microscope, the switching behaviour of individual Ag-TCNQ nanowires (NWs) is investigated in detail. For a large number of NWs, the switching between a high (OFF) and a low (ON) resistance state was successfully stimulated by negative bias sweeps. Fitting the experimental I-V curves with a Schottky emission function makes the switching features prominent and thus enables a direct evaluation of the switching process. A memory cycle including writing, reading and erasing features is demonstrated at an individual NW. Moreover, electronic failure mechanisms due to Joule heating are discussed. These findings have a significant impact on our understanding of the switching behaviour of Ag-TCNQ.
Keywords: Ag-TCNQ nanowires; in situ transmission electron microscopy; electrical switching; organic memory device; organic electronics

TEM preparation method for site- and orientation-specific sectioning of individual anisotropic nanoparticles based on shadow-FIB geometry - Vieweg, Benito; Butz, Benjamin; Peukert, Wolfgang; Klupp Taylor, Robin; Spiecker, Erdmann (Ultramicroscopy, 2012)
For the comprehensive characterization of nanoparticles cross-sectional investigation on the atomic scale by analytical and high-resolution transmission electron microscopy (TEM) is indispensable. Cross-sectioning is especially important for anisotropic nanoparticles to gain information on structure and chemistry along all important projections. We present a focused ion beam (FIB) method for site- and orientation-specific cross-sectioning of arbitrary nanoparticles that are dispersed on a substrate. By adopting a shadow geometry originally developed for thin sensitive films' protection of the specimen by a platinum layer is avoided. This enables simultaneous observation (from the front side) by the electron beam and ion-beam sectioning (from the back side of the supporting substrate) of individually selected particles with excellent accuracy on the nanometer scale. The feasibility and general applicability of the method is demonstrated by site-specific sectioning and cross-section HRTEM investigation of two types of anisotropic nanostructures: silver nanorods with five-fold twin structure and Janus-type silver patchy particles. © 2011 Elsevier B.V.
Keywords: FIB; High-resolution transmission electron microscopy; Nanoparticles; Nanorods; Patchy particles; TEM preparation

Texture evolution and microstructural changes during solid-state dewetting: A correlative study by complementary in situ TEM techniques - Niekiel, Florian; Kraschewski, Simon; Schweizer, Peter; Butz, Benjamin; Spiecker, Erdmann (Acta Materialia, 2016)
The transition of a thin film into an energetically favorable set of particles at temperatures below the melting point of the bulk material is known as solid-state dewetting. In this work the dewetting behavior of 16 nm thick discontinuous Au thin films on amorphous silicon nitride membranes is quantitatively studied by complementary in situ transmission electron microscopy techniques taking advantage of the unique capabilities of a chip-based heating system. The combination of dedicated imaging and diffraction techniques is used to investigate the interplay of grain growth and texture evolution with the process of dewetting. The results show an initial coarsening of the microstructure preceding the other processes. Texture evolution is highly correlated to material retraction and agglomeration during the following dewetting process. In-plane grain rotation has been observed, acting as an additional mechanism for orientation changes. From a methodological perspective this work demonstrates the capabilities of today's transmission electron microscopy in combination with state-of-the-art in situ instrumentation. In particular the combination of complementary information from different dedicated techniques in one and the same setup is demonstrated to be highly beneficial. (C) 2016 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Solid-state dewetting; Thin films; Texture; Grain growth; Grain rotation

The process of solid-state dewetting of Au thin films studied by in situ scanning transmission electron microscopy - Niekiel, Florian; Schweizer, Peter; Kraschewski, Simon; Butz, Benjamin; Spiecker, Erdmann (Acta Materialia, 2015)
Solid-state dewetting describes the transformation of thin films into a set of particles or droplets at temperatures well below the melting temperature of the bulk. In this work in situ scanning transmission electron microscopy has been used to study the dewetting behavior of discontinuous Au thin films (15 nm and 22 nm thick) on amorphous silicon nitride membranes at temperatures ranging from 300 °C to 600 °C. The combination of microscopic and statistical information enabled not only the qualitative discussion of the observed processes but also the quantification of the kinetics as well as the development of a model of the underlying morphological mechanism. A model-free master curve approach to the temporal evolution of the covered area at different temperatures is used to determine the activation energy of dewetting (1.04±0.14eV for the 15 nm thick film). A closer inspection reveals a multiple power law behavior, which is discussed in the frame of depercolation. Retraction of finger-like structures is found to be the dominant morphological mechanism based on the observed linear relationship between covered area and boundary length.
Keywords: Image analysis; Morphology; Solid-state dewetting; Temporal evolution; Thin films

Three-dimensional and quantitative reconstruction of non-accessible internal porosity in hematite nanoreactors using 360 degrees electron tomography - Distaso, Monica; Apeleo Zubiri, Benjamin; Mohtasebi, Amirmasoud; Inayat, Alexandra; Dudak, Michal; Koci, Petr; Butz, Benjamin; Klupp Taylor, Robin; Schwieger, Wilhelm; Spiecker, Erdmann; Peukert, Wolfgang (Microporous and Mesoporous Materials, 2017)
In the current paper, mesocrystals are used as effective precursors to design nanoreactors with different kinds of enclosed porosity. The thermal treatment of hematite mesocrystalline nanoparticles is investigated as a post-processing tool for the engineering of internal organization of hierarchical structures. The porosity of starting materials and of particles thermally treated at different temperatures is investigated by transmission electron microscopy, nitrogen sorption and 360 degrees electron tomography. Virtual Capillary Condensation and Maximum Sphere Inscription are used as independent approaches for the quantitative assessment of internal porosity. The combination of experimental evidences and simulations provides a deep understanding of the internal topology of nanoreactors upon thermal treatment of mesocrystalline particles. This new design strategy may pave the way for exploring the use of the post treated mesocrystals as carriers to encapsulate materials for optoelectronic applications. (C) 2017 Elsevier Inc. All rights reserve
Keywords: Mesocrystals; Inorganic hollow nanoparticles; Compartmentalization; Encapsulation

Transfer of Individual Micro- and Nanoparticles for High-Precision 3D Analysis Using 360° Electron Tomography - Przybilla, Thomas; Apeleo Zubiri, Benjamin; Maria Beltran, Ana; Butz, Benjamin; Machoke, Albert; Inayat, Alexandra; Distaso, Monica; Peukert, Wolfgang; Schwieger, Wilhelm; Spiecker, Erdmann (Small Methods, 2017)
A versatile approach is demonstrated, providing a general routine for an extensive and advanced 3D characterization of individually selected micro- and nanoparticles, enabling the combination of complementary and scale-bridging techniques. Quintessential to the method is the transfer of individual particles onto tailored tips using a conventional scanning electron microscope equipped with a suitable micromanipulator. The method enables a damage- and contamination-free preparation of freestanding particles. This is of significant importance for applications addressing the measurement of structural, physical, and chemical properties of specifically selected particles, such as 360° electron tomography, atom probe tomography, nano X-ray tomography, or optical near-field measurements. In this context, the method is demonstrated for 360° electron tomography of micro-/macroporous zeolite particles with sizes in the micrometer range and mesoporous alpha-hematite nanoparticles exhibiting sizes of 50–100 nm, including detailed pre- and post-characterization on the nanoscal
Keywords: 360 degrees electron tomography; dual-beam SEM/FIB; micromanipulation; pick and place; sample preparation